A metal-free approach for the synthesis of amides/esters with pyridinium salts of phenacyl bromides via oxidative C–C bond cleavage - Manasa, Kesari Lakshmi; Tangella, Yellaiah; Krishna, Namballa Hari; Alvala, Mallika (Beilstein Journal of Organic Chemistry, 2019)
An efficient, simple, and metal-free synthetic approach for the N- and O-benzoylation of various amines/benzyl alcohols with pyridinium salts of phenacyl bromides is demonstrated to generate the corresponding amides and esters. This protocol facilitates the oxidative cleavage of a C–C bond followed by formation of a new C–N/C–O bond in the presence of K2CO3. Various pyridinium salts of phenacyl bromides can be readily transformed into a variety of amides and esters which is an alternative method for the conventional amidation and esterification in organic synthesis. High functional group tolerance, broad substrate scope and operational simplicity are the prominent advantages of the current protocol.
Keywords: amidation; benzoylation; benzylamines; pyridinium salt of phenacyl bromides